RECOGNITION AND ENFORCEMENT OF MAINTENANCE DECISIONS IN ACCORDANCE WITH THE 2007 HAGUE MAINTENANCE CONVENTION: ON THE OCCASION OF THE BEGINNING OF APPLICATION OF A NEW SOURCE OF SERBIAN PRIVATE INTERNATIONAL LAW - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Starting from 1 February 2021 Serbia is under an obligation to apply the 2007 Hague Convention on the International Recovery of Child Support and Other Forms of Family Maintenance. This is a new source introducing significant changes in Serbian private international law. Apart from provisions on administrative cooperation between contracting states’ central authorities with an aim to simply and accelerate recovery of maintenance in international context, the Convention contains detailed provisions on recognition and enforcement of maintenance decisions, reasons for its refusal and, which is a particular novelty in comparison to previous international convention, procedural rules that a court of another competent body of the requested state should apply while deciding on the issue. The paper discusses the main features of the recognition and enforcement mechanism established by the Convention and, in particular, certain issues that Serbian courts might face as a result of the interaction between provisions of the Convention and Serbian law.